Oxytocin and Related Peptide Hormones: Candidate Anti-Inflammatory Therapy in Early Stages of Sepsis - Mehdi, Syed Faizan; Pusapati, Suma; Khenhrani, Raja Ram; Farooqi, Muhammad Saad; Sarwar, Sobia; Alnasarat, Ahmad; Mathur, Nimisha; Metz, Christine Noel; LeRoith, Derek; Tracey, Kevin J.; Yang, Huan; Brownstein, Michael J.; et al. (Frontiers in Immunology, 2022)
Sepsis is a potentially life-threatening systemic inflammatory syndrome characterized by dysregulated host immunological responses to infection. Uncontrolled immune cell activation and exponential elevation in circulating cytokines can lead to sepsis, septic shock, multiple organ dysfunction syndrome, and death. Sepsis is associated with high re-hospitalization and recovery may be incomplete, with long term sequelae including post-sepsis syndrome. Consequently, sepsis continues to be a leading cause of morbidity and mortality across the world. In our recent review of human chorionic gonadotropin (hCG) (1), we noted that its major properties including promotion of fertility, parturition, and lactation were described over a century ago. By contrast, the anti-inflammatory properties of this hormone have been recognized only more recently. Vasopressin, a hormone best known for its anti-diuretic effect, also has anti-inflammatory actions. Surprisingly, vasopressin's close cousin, oxytocin, has broader and more potent anti-inflammatory effects than vasopressin and a larger number of pre-clinical studies supporting its potential role in limiting sepsis-associated organ damage. This review explores possible links between oxytocin and related octapeptide hormones and sepsis-related modulation of pro-inflammatory and anti-inflammatory activities.